Ecology and Economics: Contradiction, Correlation Versus Harmony - Rustamovich, Shokirov Mubin (International Journal of Psychosocial Rehabilitation, 2020)
In the following article modern ecological issues, environmental hazards are reconsidered. Also the correlation of the ecology and economy is analyzed. The ideas of Carl Linnaeus, K.A.Timiryazev, M.T.Mileshkin are analysed through the system of comparative analysis. It has been substantiated that the recovery of the environmental chain is undergoing within the framework of the cyclic changes in the biosphere.